FENOMENA KOMUNIKASI MAHASISWA UNIVERSITAS RIAU MENJADI DRIVER MAXIM DI PEKANBARU - Lovita Riwanti; MUhammad Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research is motivated by the author's interest in the phenomenon that occurs among students. Many students, especially the final semester, choose to work part-time, one of which becomes the maxim driver. Every job has various advantages and disadvantages, and being a maxim driver also has various kinds of challenges that students will face, they must be clever in utilizing the available time, and not forgetting their main obligation as a student. Therefore, this study aims to determine the motives, communication experience and self-concept of Riau University students to become the maxim driver.            This study used a qualitative research method using a phenomenological approach and consisted of 6 informants who were selected using a purposive technique collected through in-depth interviews, observation and documentation. To perform data validity, the author uses the technique of extending observations, increasing persistence, and using reference materials.            The results showed that the motives of Riau university students to become driver maxim consisted of motives because they included the economy, adding to experience, looking for activities, inviting friends, employment and maxim uniqueness. and the hope motive, namely to ease the burden on parents and help others. Furthermore, enjoyable communication experiences include getting more tips from passengers, building new relationships, gaining customer loyalty and getting a warm attitude from passengers. And the unpleasant communication experience is getting sexual harassment, involvement in drug delivery services, getting into conflicts with other motorcycle taxis, getting selfish passengers, driver negligence on orders and experiencing technical problems. Then the self-concept of Riau University students becomes a driver maxim consisting of a positive self-concept, namely student acceptance of the profession as a maxim driver, openness to the environment and new people, good treatment of the surrounding environment and openness to experience. Meanwhile, negative self-concept consists of unfavorable treatment from the surrounding environment and tends to close oneself to experiences. Keywords : Phenomenon Communication, Maxim  Driver,Students